Tantangan dan Solusi Implementasi Kebijakan Literasi Baca Tulis di Sekolah Dasar : Studi Literatur - Ndolu, Sumardi W.; Tominggot, Klarita; Mauli, Riada G.; Sinaga, Gloria O.; Momongan, Kurnia D.; Pahoro, Silvia J. G. (Jurnal Ilmiah Wahana Pendidikan, 2025)
The implementation of reading and writing literacy policies in Primary Schools (SD) was considered a crucial strategy to cultivate a reading culture from an early age, forming the main foundation for improving educational quality. However, the execution at the school level faced significant challenges. Identified obstacles included low student reading interest, limited facilities and relevant reading collections, and insufficient teacher competence in innovative literacy methodologies. Furthermore, minimal family involvement was an external factor exacerbating the situation. The results of this study show that effective and structured interventions encompass strengthening the integrated School Literacy Movement (GLS), continuous teacher training, providing engaging leveled reading collections, proportional use of technology, and collaborative family literacy programs. Recommendations focus on policy synergy, sustainable funding, and monitoring and evaluation based on literacy indicators to ensure program continuity.